Climate change: Clinical considerations. (28th June 2019) - Haseley, Dennis
Abstract: Psychological reactions to climate change run the gamut from a sense of the need for urgent action to utter denial. This paper looks at some categories of defenses that block acknowledgement of this pressing threat. It cites the work of Renee Lertzman, an analytically oriented social scientist, whose research suggested that disavowal, negation, or denial could be deconstructed and viewed as defenses against intolerable anxieties, feelings of helplessness and disappointment, loss and guilt, and warded‐off wishes for agency and reparation. Clinical examples and personal self‐reflection are employed to posit that when anxiety over climate change, a serious disquiet in its own right, gets confused with childhood traumatic anxiety, with its attendant feelings of helplessness, smallness, hopelessness, shame, isolation, and useless rage, then dysfunctional defenses and affects are more likely to come to the fore. In contrast to this, realistic anxiety over our changing climate and need to shift from a carbon‐based culture can be made more tolerable and can allow one to face the uncertain future, to feel one's feelings, to work them through, to share them without shame, and to feel a certain amount of agency in confronting the climate future and working to cope with it, both individually and societally. Finally, the paper suggests that we clinicians need to listen with new awareness to patients' references to and defenses against climate change, as not simply displacements but also as allusions to a looming reality that is a thing in itself. It is suggested that although we cannot impose our agendas on our patients, as climate change disavowal breaks down, we do have in our tool kit ways of helping our patients with it, depending of course very much on the state of our own disavowal.